2019
DOI: 10.1155/2019/3194912
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Bilateral Asymmetry in the Humerus of Human Skeletal Specimen

Abstract: Several studies have established a relationship between morphological and behavioral asymmetry making investigations of bilateral bone asymmetry an attractive and important research area. The purpose of this study was to investigate bilateral asymmetry patterns of skeletal specimen from five geographical locations (Rwanda, Burundi, Congo, Kenya, and Uganda) at Galloway Osteological Collection, Department of Anatomy, School of Biomedical Sciences, Makerere University College of Health Sciences. The angle of tor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
0
5
0
1
Order By: Relevance
“…Embora comparações das medidas e estimativas antropométricas entre os hemicorpos têm sido objeto de pesquisas recentes, de modo geral, as investigações não incluem medidas de PS nas análises, e seus objetivos estão relacionados à avaliação de treinamento, força e movimento muscular. Todavia, estudos têm mostrado assimetrias entre os braços como maior massa, 25 e maior dimensão, peso e espessura do úmero 26 do braço dominante (direito) em comparação ao esquerdo. Por outro lado, Macedo et al 27 compararam DCT entre os lados dominante e não dominante em grupos com comprometimento unilateral e controle.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Embora comparações das medidas e estimativas antropométricas entre os hemicorpos têm sido objeto de pesquisas recentes, de modo geral, as investigações não incluem medidas de PS nas análises, e seus objetivos estão relacionados à avaliação de treinamento, força e movimento muscular. Todavia, estudos têm mostrado assimetrias entre os braços como maior massa, 25 e maior dimensão, peso e espessura do úmero 26 do braço dominante (direito) em comparação ao esquerdo. Por outro lado, Macedo et al 27 compararam DCT entre os lados dominante e não dominante em grupos com comprometimento unilateral e controle.…”
Section: Discussionunclassified
“…Although comparisons of anthropometric estimations and measurements between hemi-bodies have been the object of recent research, most investigations do not include BP measurements in the analysis, and their objectives are related to the evaluation of training, and muscle strength and movement. However, studies have shown an asymmetry between the arms, such as greater mass, 25 and bigger, heavier, and thicker humerus in the dominant (right) arm 26 compared with the left arm than the left one. 26 On the other hand, Macedo et al 27 compared TS thickness between dominant and non-dominant sides in individuals with cerebral palsy and spastic hemiplegia and control subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Bilateral symmetry was evaluated to support left-side analysis of samples for this study. Bilateral symmetry of paired morphological traits is a correspondence in size, shape, and relative position of one side to the opposite side [ 13 ]. Significant deviation, referred to as bilateral asymmetry, may affect morphoscopic and morphometric analysis by distorting, delaying, or speeding up the skeletal markers used for biological estimations [ 13 , 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…Bilateral symmetry of paired morphological traits is a correspondence in size, shape, and relative position of one side to the opposite side [ 13 ]. Significant deviation, referred to as bilateral asymmetry, may affect morphoscopic and morphometric analysis by distorting, delaying, or speeding up the skeletal markers used for biological estimations [ 13 , 32 ]. Multiple factors can influence the prevalence and expression of asymmetry (e.g., genetic, environmental perturbations, handedness, biomechanical, etc.)…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, there remains disagreement in the literature whether, in addition to this high interindividual variability of humeral torsion, there are also intraindividual side differences in humeral torsion. For example, some authors have observed a lower humeral torsion in the dominant arm [ 22 , 23 , 24 , 25 , 26 , 27 ], whereas other authors have not found a significant side difference [ 6 , 11 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Interpretation Of Ultrasonographic Measurementsmentioning
confidence: 99%